Cobalt chloride exposure dose dependently induced hepatotoxicity through enhancement of cyclooxygenase-2 (COX-2)/B- cell associated protein X (BAX) signaling and genotoxicity in wistar rats (2017)
Cobalt chloride (CoCl2) is one of the many environmental contaminants, used in numerous industrial sectors. It is a pollutant with deadly toxicological consequences both in developing and developed countries. We investigated toxicological impact of CoCl2 on hepatic antioxidant status, apoptosis, and genotoxicity. Forty Wistar rats were divided into four groups, 10 rats per group: Group 1 served as control and received clean tap water orally; Group 2 received CoCl2 solution (150 mg/L); Group 3 received CoCl2 solution (300 mg/L); and Group 4 received CoCl2 (600 mg/L) in drinking water for 7 days, respectively. Exposure of rats to CoCl2 led to a significant decline in hepatic antioxidant enzymes together with significant increase in markers of oxidative stress. Immunohistochemistry revealed dose-dependent increase in cyclooxygenase-2 and BAX expressions together with increased frequency of Micronucleated Polychromatic Erythrocytes. Combining all, CoCl2 administration led to hepatic damage through induction of oxidative stress, inflammation, and apoptosis.